2017
DOI: 10.1088/1755-1315/80/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of beam - column joint with steel fibre reinforced concrete under seismic loading

Abstract: Earthquakes not only kill the human beings but the structures too. Considering this above fact, there is a necessity to take care of the beam column joint region in a structure. Under seismic excitation, the bar segment joint district is subjected to even and the vertical shear force extents are normally commonly greater than those in the adjoining bits of the structural segments. In the event that the joint is not precisely nitty gritty, the shaft segment joint may end up plainly frail. To keep this, an adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Experimental test results also indicated that a reinforced UHPFRC beam-column joint has a higher initial cracking strength and shear carrying capacity [23]. Furthermore, compared to conventional reinforced beam-column joints, steel fiber reinforced beam-column joints have better ductility, load-carrying capacity, energy dissipation, and strength [24].…”
Section: Introductionmentioning
confidence: 94%
“…Experimental test results also indicated that a reinforced UHPFRC beam-column joint has a higher initial cracking strength and shear carrying capacity [23]. Furthermore, compared to conventional reinforced beam-column joints, steel fiber reinforced beam-column joints have better ductility, load-carrying capacity, energy dissipation, and strength [24].…”
Section: Introductionmentioning
confidence: 94%
“…An experimental study was carried out by Prasanna et al (2017). The experimental study focuses on the behavior of M20 concrete in beam-column joint for seismic loading.…”
Section: Introductionmentioning
confidence: 99%